Faktor Penyebab Keterlambatan Perpanjangan Sertifikat Keselamatan Kapal Tugboat Pada KSOP Kelas I Balikpapan - Nur Hapipah; Muhammad Azhar Shauqy; Arif Fuddin Usman; Febrian James; Rahman Raising (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
This research uses a qualitative method with a descriptive approach and data presentation in the form of Fish Bone diagrams with observation, documentation, and interview methods. The results of this study show that there are problems that occur in the process of extending the safety certificate of tugboats at KSOP Class I Balikpapan, namely in the lack of accuracy, less efficient, and less optimal in the process of extending the safety certificate of tugboats, in the results of the inspection report there is a lack of equipment on the royal tb 7 ship, lack of maintenance of equipment on board. The solution to improve performance in the process of tugboat safety certificate extension at KSOP Class I Balikpapan is by providing evaluation, training to develop skills, in the manual system it is recommended to be changed into an electronic system in order to optimize and streamline time in the payment process, and on the shortcomings on board are given evaluation and training on the importance of sailing safety to reduce the risk of accidents at sea, checking equipment that is almost expired, and conducting regular maintenance.